تحديات إستخدام الذكاء الإصطناعي في إدارة الضرائب - عيسى كريم; مختار دادة; عبد المطلب خالدي; هشام عقيب (جامعة الوادي university of eloued, 2024)
"تهدف هذه الدراسة الى دراسة تحديات استخدام الذكاء الاصطناعي في إدارة الضرائب، لمعالجة هذا البحث اعتمدنا على المنهج الوصفي لتوضيح الإطار النظري لكل من الذكاء الاصطناعي وإدارة الضرائب، أما الجانب التطبيقي فقد اعتمدنا على منهج دراسة حالة من خلال تصميم استبيان تضمنت الجوانب الرئيسية لمحاور البحث، وقد تم توزيع 30 استمارة على مجموعة من موظفي أدارة الضرائب، وبعد تحليل النتائج توصلت الدراسة الى: -يؤثر استخدام الذكاء الاصطناعي في إدارة الضرائب عند مستوى الدلالة (α≤ 0.05) بمديرية الضرائب بالوادي. -تؤثر قدرة الادارة في إدارة الضرائب عند مستوى الدلالة (α≤ 0.05) بمديرية الضرائب بالوادي. -تؤثر سلوك المستخدم في إدارة الضرائب عند مستوى الدلالة (α≤ 0.05) بمديرية الضرائب بالوادي. -تؤثر التدريب والتطوير في إدارة الضرائب عند مستوى الدلالة (α≤ 0.05) بمديرية الضرائب بالوادي. -تؤثر توفر الخبراء في إدارة الضرائب عند مستوى الدلالة (α≤ 0.05) بمديرية الضرائب بالوادي. " "Summary This study aims to study the challenges of using artificial intelligence in tax administration. To address this research, we relied on the descriptive approach to clarify the theoretical framework for both artificial intelligence and tax administration. As for the applied aspect, we relied on a case study approach by designing a questionnaire that included the main aspects of the research axes. 30 questionnaires were distributed to a group of tax administration employees, and after analyzing the results, the study concluded: -The use of artificial intelligence affects tax administration at the level of significance (α≤ 0.05) in El-Oued Tax Directorate. The administration's ability to administer taxes has an impact at the significance level (α≤ 0.05) in El-Oued Tax Directorate. -It affects user behavior in tax administration at the significance level (α≤ 0.05) in El-Oued Tax Directorate. -The effect of training and development on tax administration at the significance level (α≤ 0.05) in El-Oued Tax Directorate. The availability of experts in tax administration affects the significance level (α≤ 0.05) in El-Oued Tax Directorate. Keywords: artificial intelligence, tax management. "
مذكرة ماستر
Keywords: الذكاء الاصطناعي، إدارة الضرائب; artificial intelligence; tax management